pengaruh kerjasama tim dan komunikasi terhadap kinerja karyawan pada departemen preparation - Irawati, Marsha Ayunita; Hafizni, Rihan; Mumpuni, Yovita Mumpuni (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2023)
The purpose of this research is to analyze the effect of teamwork and communication on employee performance in the preparation department of PT Kanindo Makmur Jaya Jepara. The population in this study was 250 employees, while the sample in this study was 150 respondents using the Sloven formula. The sampling technique uses a purposive sampling method. The independent variables in this research are teamwork and communication, while the dependent variable is employee performance. The data analysis method in this research uses validity tests, reliability tests, multiple linear regression analysis, model feasibility tests, partial tests, and determination tests. The results of this research prove that the teamwork variable has a significant effect on employee performance, this is proven by the results of the t test which shows a regression coefficient value of 0.170 and a significance value of 0.010 <0.05. The communication variable has a significant effect on employee performance, this is proven by the results of the t test, which obtained a regression coefficient value of 0.680 and a significance value of 0.000<0.05. Based on the results of this research, it can be concluded that Teamwork and Communication have a significant effect on the Performance of PT Preparation Department Employees. Kanindo Makmur Jaya Jepara. Suggestions that can be given to PT. Kanindo Makmur Jaya, especially in the preparation department, can maintain teamwork and communication so that the performance of its employees can always be good and improve so that production activities can run smoothly.